2022
DOI: 10.1186/s12936-022-04390-5
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural determinants of malaria risk, prevention, and care-seeking behaviours among forest-goers in Cambodia

Abstract: Background Cambodia has made significant progress towards achieving malaria elimination by 2025. Cases continue to decrease and are primarily concentrated in forested areas. Forest-goers are most at risk of malaria due to their proximity to the forest, poor sleeping conditions, frequent mobility, and distance from health services. Consistent use of long-lasting insecticidal nets or hammock nets (LLINs/LLIHNs), early diagnosis and treatment of cases are central to reducing disease burden. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The forest goers who refused to take a second dose reported that they had stopped their visits to the forest. It was difficult to identify frequent forest goers, mainly because of the nature of work [ 35 ]. Forest workers are recognized to be a vulnerable population in terms of the malaria risk, and delayed treatment seeking behaviour including uptake of community-based health services offered by VMWs and MMWs [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The forest goers who refused to take a second dose reported that they had stopped their visits to the forest. It was difficult to identify frequent forest goers, mainly because of the nature of work [ 35 ]. Forest workers are recognized to be a vulnerable population in terms of the malaria risk, and delayed treatment seeking behaviour including uptake of community-based health services offered by VMWs and MMWs [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%